2013
DOI: 10.1016/j.juro.2012.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Genitourinary Injuries in the United States from 2002 to 2010

Abstract: Purpose We describe the epidemiological features of pediatric genitourinary injuries, and determine the products and events that may predict an increased risk of genitourinary injury during childhood. Materials and Methods The National Electronic Injury Surveillance System was queried to identify children 18 years or younger who sustained genitourinary injuries and presented to emergency departments in the United States between 2002 and 2010. Demographics and injury characteristics of these children were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…This was similar to our observations in the pediatric population, in which 92% of patients were treated on an outpatient basis and internal GU organ injury was specified in less than 4% of all injury presentations. 19 We observed that older patients had the highest inpatient admission rates, possibly due to comorbidities that make this cohort more vulnerable after injury. GU internal organ injury also increased admission with traumatic injury to the kidney carrying a 55.2% inpatient admission rate.…”
Section: Discussionmentioning
confidence: 70%
“…This was similar to our observations in the pediatric population, in which 92% of patients were treated on an outpatient basis and internal GU organ injury was specified in less than 4% of all injury presentations. 19 We observed that older patients had the highest inpatient admission rates, possibly due to comorbidities that make this cohort more vulnerable after injury. GU internal organ injury also increased admission with traumatic injury to the kidney carrying a 55.2% inpatient admission rate.…”
Section: Discussionmentioning
confidence: 70%
“…Although renal injuries accounted for only 3.5% of all pediatric GU injuries, it was responsible for 25.7% of hospital admissions in this cohort. [26]…”
Section: Organsmentioning
confidence: 99%
“…Prior studies have noted that sporting injuries in particular are a common source of genitourinary (GU) injury, especially among pediatric and young adult cohorts. 1,2 In particular, current investigations have provided some important insights into the nature and likelihood of such injuries by focusing on specific sporting activities 311 and isolated GU organs. 1221 However, the overall epidemiology of sporting GU injury remains unknown.…”
mentioning
confidence: 99%